Report on the main activities undertaken and preliminary findings emerging from research on the CGIAR Targeting Agricultural Innovations and Ecosystem Services in the northern Volta basin (TAI) project - Boundaogo, M.; Brauman, Kate A.; Chaplin-Kramer, Rebecca; Daré, W.; DeClerck, Fabrice A.J.; Fremier, Alexander K.; Gordon, L.; Katic, P.; Kizito, Fred; Lanzanova, D.; Luedeling, Eike; Johnson, J.; et al. (2016)
The CGIAR Water, Land and Ecosystems research project on Targeting Agricultural Innovations and Ecosystem Services in the northern Volta basin (TAI) is a two year project (2014-2016) led by Bioversity International in collaboration with 11 institutes: CIAT, CIRAD, International Water Management Institute (IWMI), King’s College London (KCL), SNV World Burkina Faso (SNV), Stanford University, Stockholm Resilience Centre (SRC), University of Development Studies Ghana (UDS), University of Minnesota, University of Washington, and the World Agroforestry Institute. We are working with communities across Centre-Est Burkina Faso and Upper-East Ghana to gather empirical data, test research methodologies and co-develop knowledge on solutions to ecosystem service management challenges. Results from the project are still emerging and will continue to do so into 2017 as the team finish analysing the data and writing up their findings. This report presents the main activities accomplished and preliminary headline messages from the first 18 months of the project. Final results from the project will be made available in 2017 on the WLE website.